Continent-wide recent emergence of a global pathogen in African amphibians - Ghose, Sonia L.; Yap, Tiffany A.; Byrne, Allison Q.; Sulaeman, Hasan; Rosenblum, Erica Bree; Chan-Alvarado, Alan; Chaukulkar, Shruti; Greenbaum, Eli; Koo, Michelle S.; Kouete, Marcel T.; Lutz, Kurt; McAloose, Denise; et al. (Frontiers in Conservation Science, 2023)
Emerging infectious diseases are increasingly recognized as a global threat to wildlife. Pandemics in amphibians, caused by the fungal pathogen Batrachochytrium dendrobatidis (Bd), have resulted in biodiversity loss at a global scale. Genomic data suggest a complex evolutionary history of Bd lineages that vary in pathogenicity. Africa harbors a significant proportion of global amphibian biodiversity, and multiple Bd lineages are known to occur there; yet, despite the decline of many host species, there are currently no reported Bd-epizootics there. Here, we describe the historical and recent biogeographical spread of Bd and assess its risk to amphibians across the continent of Africa. We provide a 165-year view of host-pathogen interactions by (i) employing a Bd assay to test 4,623 specimens (collected 1908–2013); (ii) compiling 12,297 published Bd records (collected 1852–2017); (iii) comparing the frequency of Bd-infected amphibians through time by both country and region; (iv) histologically identifying evidence of chytridiomycosis; (v) genotyping Bd lineages, and (vi) using a habitat suitability model to assess future Bd risk. We found a pattern of Bd emergence beginning largely at the turn of the century. From 1852–1999, we found low Bd prevalence (3.2% overall) and limited geographic spread, but after 2000 we documented a sharp increase in prevalence (18.7% overall), wider geographic spread, and multiple Bd lineages with indications of hybridization. We found that Bd risk to amphibians was highest in much of eastern, central, and western Africa. Our study documents a largely overlooked yet significant increase in a fungal pathogen that could pose a threat to amphibians across an entire continent. We emphasize the need to bridge historical and contemporary datasets to better describe and predict host-pathogen dynamics over larger temporal scales.